Flexural Stress-Strain Behavior of RC Beams made with Partial Replacement of Coarse Aggregates with Coarse Aggregates from Old Concrete: Part-2: Rich Mix - Oad, M.; Buller, A. H.; Memon, B. A.; Memon, N. A.; Sohu, S. (Engineering, Technology & Applied Science Research, 2018)
Crowded city centers pose serious problems of infrastructure and associated facilities. Construction industry is obliged to opt for vertical construction in place of short height structures in order to meet with the needs. This leads to the generation of huge quantities of demolishing waste whose management is a serious issue. One of its best uses is its utilization in new concrete. Concrete is widely used in construction industry. Normally 1:2:4 mix is used, but the use of rich mix is also common in columns and elsewhere. Therefore, this research work focuses on evaluating the flexural stress-strain behavior of rich concrete mix beams made with 50% replacement of natural coarse aggregates with coarse aggregates from old concrete. A total of 12 reinforced concrete beams 1:1.5:3 ratio mix and 0.54 w/c ratio are prepared in two batches in 0.9mx0.15mx0.15m beams. In the first batch, natural coarse aggregates are replaced in 50% with coarse aggregates from demolished concrete and the second batch contains beams made with all-natural coarse aggregates. To reinforce the beams, 2#4 deformed bars are used in compression and tension zone along with #3 stirrups at 15cm c/c all along the length of the beam. In each batch, half of the beams are cured for 7 days and half for 28 days. After curing, all beams are tested for load, deflection, and strain in a universal load testing machine. All parameters are recorded at regular intervals and cracking and failure patterns are monitored. From obtained results, it is analyzed that the beams presented 11.68% reduction in flexural capacity. Cracking pattern and failure mode of the beams is similar to those of the control specimen.